Population dynamics of bearded croaker Johnius dussumieri (Cuvier, 1830) from Pakistani waters - Baset, Abdul; Liu, Qun; Liao, Baochao; Waris, Abdul; Yanan, Han; Qingqing, Zhang; Ahmad, Imtiaz (Journal of Fisheries, 2020)
In this study the length frequency data of 2510 bearded croaker Johnius dussumieri (Cuvier, 1830), collected from the coast of Pakistan during 2015, were analysed. Total length of the specimens (male and female combined) varied from 4 to 25 cm with dominant individuals ranged between 12 and 15 cm whereas the body weight varied between 3 and 155 g. The length frequency data were analysed for the estimation of population dynamics and the power coefficient b of length weight relationship was estimated as 2.83. Other measurements were as follows: asymptotic length, L∞ = 26.25 cm; growth coefficient, K = 1.00 year–1; total mortality, Z = 2.43 year–1; and natural mortality, M = 1.82 year–1. The fishing mortality (F) and exploitation ratio (E) were 0.61 year–1 and 0.251 respectively. The Biological Reference Points (BRPs) with Gulland method for this fishery (Fopt) was estimated 1.82 year–1 which is higher than current fish mortality. Therefore the present study shows that the J. dussumieri fishery is safe in Pakistan.